The Relativism in Language Study: Face Threatening Acts and Politeness Found in Kediri - Mohammad Muhyidin (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2022)
The rising or decreasing level of politeness impacts the intensity of human behavior. By using the theory of Brown and Levinson's model of politeness and civility theoretical model of Robin Lakoff, this paper aims to describe the Face Threatening Acts performed in public notices in Kediri. This study used the qualitative method because it focuses more on the analysis of written data rather than numbers. This study looks into public notices written by people in public places. The writer uses the theory of Relativism and politeness. The findings show that using more power, being forced, and playing with an adversary can create discomfort. An example can be seen from the public notice “Angel Ngeyel “JOTOS” (English translation: Those who are disobedient will get punched). People who read this notice will feel uncomfortable and it may potentially influence the readers to think and act rudely. It affects people's behavior. Another notice reads “Mlebu kene SETOR NYOWO”, which is about “Zona Rawan Pukul”. This means that people must not enter the village because of the pandemic Covid 19. If they insist to enter the village, they will die or lose their lives. Based on the theory of Robin Lakoff, the notice tends to have declined politeness. This phenomenon is a result of unbridled democracy so everyone feels entitled to talk about anything, the higher frequencies that do not use polite language in the mass media and electronic, and depletion of mutual respect between people. As a result, the behavior of this nation into insolent, and destructive, and the hostility between people are increasingly visible and tend to be light publicly.